(untitled) (CIPEEX, 2022)
THE CONSUMPTION OF COOKING OIL IS WIDELY USED IN FOOD PREPARATION IN CAFETERIAS, RESTAURANTS, HOMES AND OTHERS. HOWEVER, MANY DO NOT KNOW WHERE AND HOW TO PROPERLY DISPOSE OF THIS MATERIAL, WHICH CAN CAUSE SEVERAL SERIOUS PROBLEMS FOR THE ENVIRONMENT. BASED ON THESE QUESTIONS, PROG လLEO AIMS TO BE AN APPLICATION TO IDENTIFY CORRECT DISPOSAL STATIONS, REDUCING THE TIME SPENT FOR ITS EXECUTION. THE APP WILL BE SIMPLE AND INTUITIVE, SHOWING CLEAR INFORMATION OF EACH FUNCTIONALITY WITH A STEP-BY-STEP GUIDE, SO THAT THE APP IS ACCESSIBLE TO MORE PEOPLE. THE PLATFORM WILL USE THE CURRENT LOCATION OF THE USER AND THE CATEGORY OF DISPOSAL AS SEARCH PARAMETERS, OBTAINED THROUGH THE INFORMATION ON THE USER’S DEVICE. THESYSTEM WILL HAVE TWO CATEGORIES OF EXCHANGE, FOR CASH OR BENEFITS (NEW OIL OR WATER DISCOUNTS). THE USER CAN ALSO CHOOSE TO DONATE TO NEEDY INSTITUTIONS. SUCH EXCHANGES MAY BE ARRANGED THROUGH THE INTEGRATED AND ENCRYPTED CHAT. THROUGH THIS WORK, THE MVP (MINIMUM VIABLE PRODUCT) WILL BE DEVELOPED TO VALIDATE THE PROPOSAL AND IDENTIFY NEW FEATURES WITH THE COMMUNITY AND FEASIBILITY OF IMPLEMENTATION.